2006
DOI: 10.1080/00365540600786507
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiotic susceptibility of Acinetobacter baumannii, Pseudomonas aeruginosa and Klebsiella pneumoniae in Estonian intensive care units in comparison with European data

Abstract: This prospective cohort study was performed from April to December 2003 for the purpose of collecting a maximum of 50 non-duplicate isolates of Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae from each of 4 ICUs to determine minimum inhibitory concentrations. The most prevalent species were Enterobacteriaceae (13%), K. pneumoniae and A. baumannii (both 12%). 60% of A. baumannii strains were susceptible to ampicillin/sulbactam and cefepime, 95% to meropenem and imipenem, and 75% to am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…AMS has comparable activity to AMP against bacteria that are resistant to ␤-lactam antibiotics as a result of mechanisms other than ␤-lactamase production [17], such as S. pneumoniae. Table 1 summarises recent AMS susceptibility data [19][20][21][22][23][24].…”
Section: Microbiology and In Vitro Activitymentioning
confidence: 99%
“…AMS has comparable activity to AMP against bacteria that are resistant to ␤-lactam antibiotics as a result of mechanisms other than ␤-lactamase production [17], such as S. pneumoniae. Table 1 summarises recent AMS susceptibility data [19][20][21][22][23][24].…”
Section: Microbiology and In Vitro Activitymentioning
confidence: 99%
“…Furthermore, in the MYSTIC report from 48 European hospitals for isolates from the period of 2002 to 2004 (38), 27% and 30% of isolates were resistant to meropenem and imipenem, respectively. Therefore, such high percentages of resistance in the current study, compared to the previous findings in Taiwan as well as in other countries (16,21,27,38), may suggest that the prevalence of the isolates in the A. calcoaceticus-A. baumannii complex that are resistant to carbapenems has recently been increasing in Taiwan.…”
Section: Discussionmentioning
confidence: 38%
“…Previous studies conducted in intensive care units (ICUs) of several teaching hospitals in Taiwan had already indicated that the percentage of resistance to imipenem in A. baumannii was increasing, from 22% in 2000 to 25% in 2005 (16,21). In other countries, such as Estonia, 5% of A. baumannii strains were resistant to meropenem and imipenem (27). Furthermore, in the MYSTIC report from 48 European hospitals for isolates from the period of 2002 to 2004 (38), 27% and 30% of isolates were resistant to meropenem and imipenem, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As the collection contained a large number of Pseudomonas strains, and increased carbapenem resistance is a problem in Estonian medical settings [37], we included a member of this group of antibiotics, meropenem, in the resistance testing.…”
Section: Resultsmentioning
confidence: 99%